Effect of local exercise and vessel occlusion on fibrinolytic activity. Issue 4 (April 1977) - Rennie, J A; Bennett, B; Ogston, D
Abstract : Arterial occlusion of the upper limb did not affect the fibrinolytic activity in the venous blood of that limb; venous occlusion associated with venous distension resulted in a marked rise in activity. Local fibrinolytic activity was increased substantially by active exercise; passive exercise induced a smaller increase. Active exercise undertaken during arterial occlusion did not result in a rise in activator level. It is concluded from these results that blood flow into the venous system rather than accumulation of metabolites is responsible for the increased release of activator into the blood during local exercise and vessel occlusion.